PEMBELAJARAN MENYENANGKAN DALAMMENULIS-APRESIASISASTRA - sariban sariban (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2016)
The fun learning in literature can be designed with the teacher perceives the students as a creative individual. Teachers did not do much doctrinal. Teacher more facilitated the students to want to know several things. Teacher guides the students to discover the answer for students’ questions. From theorists and empirical studies, literary fun learning can be designed as follows. First, using the environment as a potential medium for learning literature. For example, when appreciating a short story with a theme of peace of life, set in the countryside according to the environment students. Second, the themes that have adapted to a child's development, such as the themes of love. With the theme that the students could be invited to sit in the garden in a regular position. Students can talk at length about love, flowers, butterflies, beetles, beauty, peace, engrossing, because the problems of love are part of it. Third, a variety of learning are needed in teaching literature. To enjoy valuable religious poetry, students could be invited to the mosque or prayer room of the school. Teachers and students discussed the "taste" and relaxed about the religiosity that is contained in the poem we choose. Students couldtalk about God, revelation, book, nature, destiny, fate, and the like. Utilization background was absolutely in the learning environment. The themes that were being faced by the students in making student life easier and appreciates creative writing. Therefore, 'mood condition the students' learningwasthe key to literary fun.